PEMBENTUKAN KELAS KATA VERBA PADA TEKS EKSPOSISI DALAM BUKU BUDI WALUYO: BAHASA DAN SASTRA INDONESIA KELAS VIII SMP DAN MTS - Hafzhaniyah, Nur Alfi; Pertiwi, Dora Hatika; Nuryani, Nuryani (Ma Chung Press, 2024)
This study aims to determine the formation of verbs in the exposition text in the book Budi Waluyo Bahasa dan Sastra Indonesia Kelas VIII SMP dan MTS. This research was conducted with qualitative descriptive research. The data used in this study are verbs and the source of the data is in the book Budi Waluyo: Indonesian Language and Literature Class VIII SMP and MTS. The technique used in collecting data in this research is the analysis technique on the exposition text which contains a verb. The results of data analysis are presented using ordinary words. The forms found from the data source include the original verb and the derived verb. Derived verbs formed by affixation and verbs formed by reduplication. Affixes forming verbs include, meN-, meN-kan, meN-i, di-, ter- and ber-an. In addition, there are verbs related to nouns, namely active and passive verbs and verbs related to arguments, namely copulative verbs and equative verbs.